Pengaruh Kualitas Pelayanan dan Kualitas Produk Makanan terhadap Kepuasan Konsumen pada Tempat Makan Sego Pedas Basman Cabang Telagasari - Fitria Sopiatul Lutfi; Aji Tuhagana; Zenita Apriani (Pusat Riset dan Inovasi Nasional, 2024)
This paper aims to determine the effect of service quality and product quality on customer satisfaction at the Sego Pedas Basman Telagasari branch. The study used a quantitative approach with a survey technique, where data was collected by distributing questionnaires to 96 respondents who were consumers of Sego Pedas Basman. The results of the study indicate that the quality of food products has a significant partial effect on consumer satisfaction, especially in terms of taste, texture, cleanliness, and presentation. In addition, friendly, fast, and attentive service quality also contributes to forming a positive consumer experience. Simultaneously, both variables, service quality and product quality, have a significant effect on customer satisfaction, with a coefficient of determination of 71.2%. This shows that both factors provide a dominant contribution to consumer satisfaction, while the remaining 24.8% is influenced by other factors outside this study. These findings are expected to be a reference for better service and product development strategies.